2017
DOI: 10.1016/j.jaci.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Pru p 3 IgE-binding activity by selective free fatty acid-interaction

Abstract: interaction with pruritogens, including SP and compound 48/80, we evaluated LL-37-induced itch using the mouse cheek model. As opposed to pruritogens, which induce scratching in this model, LL-37 does not induce scratching (see Fig E8 in this article's Online Repository at www.jacionline.org).The data presented here demonstrate that SP and compound 48/ 80 activate native Mrgprs but fail to activate Mrgprs in which a single amino acid residue was mutated. In contrast, LL-37 activates both native receptor and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…Although tertiary structures of some nsLTPs have already been resolved, there is still a lack of experimental knowledge regarding the impact of ligands on the protein 3D structure. Since it has been shown that the ligand binding specificity can vary among protein family members 10,20 and that this is an important factor regarding nsLTP allergenicity 30 , we investigated the ligand binding ability of the major allergen from walnut, Jug r 3. We also investigated the interaction of Jug r 3 with OLE by NMR technique and an in silico docking program to model the Jug r 3-OLE complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tertiary structures of some nsLTPs have already been resolved, there is still a lack of experimental knowledge regarding the impact of ligands on the protein 3D structure. Since it has been shown that the ligand binding specificity can vary among protein family members 10,20 and that this is an important factor regarding nsLTP allergenicity 30 , we investigated the ligand binding ability of the major allergen from walnut, Jug r 3. We also investigated the interaction of Jug r 3 with OLE by NMR technique and an in silico docking program to model the Jug r 3-OLE complex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the interaction between free fatty acids and nsLTPs affects the local conformation of the protein 29 . We have recently demonstrated that in Pru p 3 such interactions increase also the allergenic potential of the protein 30 . However, experimental structural data on the atomic level remained limited.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, unsaturated FA (oleic, linoleic, and elaidic acid) and short chain saturated lauric acid (C12) were confirmed to bind to Pru p 3 by 1,8-ANS-competition assays ( 31 ). Binding of oleic but not stearic acid (saturated C18) increased IgE-reactivity and basophil activation by conformational changes.…”
Section: Interaction Of Lipids With Allergenic Food Nsltps Likely Effmentioning
confidence: 99%
“…In summary, several FAs, likewise saturated lauric acid and unsaturated oleic acid ( 31 ) as well as palmitic acid ( 29 ), and phytosphingosine ( 33 ) were described as ligands for Pru p 3 (Table 1 ). The conjugation of lipids to nsLTPs may influence the IgE-binding capacity by structural modification of allergens ( 31 ). So far, the effect of lipids on the stability of allergens is discussed controversially.…”
Section: Interaction Of Lipids With Allergenic Food Nsltps Likely Effmentioning
confidence: 99%
“…Understanding how to reduce side effects during immunotherapy is a highly relevant topic which was addressed by a research group from the Medical University of Vienna . In particular, the work focused on the characterization by NMR, at the CERM facility, of the lipid binding properties of the major peach allergen named Pru p 3, providing evidence that upon ligand binding, the allergen undergoes local structural changes which modulate its allergenic activity.…”
Section: Accelerating Science Outputmentioning
confidence: 99%